Reliability analysis for TO-247 multilayered power module packaging under mechanical oscillation based on finite element method. (March 2021) - Ghaderi, Davood
Abstract: This paper presents the simulation and hardware test results for determining the fatigue life of the solder joints of a printed circuit board (PCB) including a DC to AC inverter circuit with six power metal oxide semiconductor field effect transistors (MOSFETs) by using the finite element method (FEM) under different vibration effects. This board is exposed under different angles by a vibration machine. The selected angles were performed on the power module to find the maximum stress points of the power module for different vibration frequencies. The results indicate that the maximum stress is observed at the corners of the solder layer. The stress of the solder joints significantly increases when the input frequency increases, and the failure, voids generation and crack formation and propagation are more observable under this condition. Furthermore, the loading direction changes show that the peeling stress of the solder layer is directly affected by lower angles. The shear stress occurs in lower angles of loading directions, and this situation results in the peeling stress. The simulation investigations are proved by the experimental results in the study. According to the observations, the fatigue effects result in the coalescence and the void growths in lower angles of vibration loadings. The paper also investigates the normal loading condition of the power inverter circuit, and the highest reliability is obtained compared to all other experimental tests. Highlights: The maximum stress is observed at the corners of the solder layer. The failure, voids generation and crack formation and propagation are more observable for higher input frequencies. The loading direction changes show that the peeling stress of the solder layer is directly affected by lower angles. The shear stress occurs in lower angles of loading directions, and this situation results in the peeling stress. The fatigue effects result in the coalescence and the void growths in lower angles of vibration loadings.